Neonatal Rhabdomyolysis: A Case Report and Review of the Literature - Uzun, Özlem Ünal; Çınar, Müge; İster, Meral Bahar; Eşgi, Merve; Kara, Bülent; Pehlevan, Özge Serçe (Neuropediatrics, 2025)
Rhabdomyolysis is a potentially life-threatening condition in pediatric patients, often triggered by various factors, such as infections, trauma, hereditary metabolic disorders, and certain medications. Elevated creatine kinase levels are commonly observed in newborns and are often attributed to factors such as hypoxia, labor dystocia, and birth trauma. However, rhabdomyolysis in this population is rare and typically associated with hereditary metabolic disorders, medications, or infections. In this report, we describe the case of a neonate diagnosed with very long-chain acyl-CoA dehydrogenase deficiency after markedly elevated creatine kinase levels and rhabdomyolysis were identified during the neonatal period. Additionally, we suggested a guideline for the evaluation of creatine kinase elevation and rhabdomyolysis in neonates.
Keywords: very long-chain acyl-CoA dehydrogenase deficiency; rhabdomyolysis; newborn